Internal and external factors in female athletes who returned to competition and - Sumi, K.; Ishiguro, E.; Sawai, K.; Mano, Y. (Journal of High Performance Sport, 2025)
The percentage of women in Japanese society who continue to work after childbirth is gradually increasing. Consequently, an increasing number of female athletes want to continue competing after childbirth. It is difficult for women to continue competing after giving birth, which is the current issue in Japan. In this study, we interviewed 12 female athletes who continued to compete after childbirth and competed at the world's top level. We analyzed their attitudes and the support they received from their surroundings, and explored the factors that made it possible for them to continue competing. The results revealed that "flexible goal setting," "freedom from gender roles," "support from family members other than partners," "role models," and "existence of lower category competitions" were important for continuing to compete.